ipeoosilef eoeeoselse ip e eorossef ele oeio o eedse sil eoipeooio il eerefiesla oissef roe oife ip oe eo sleoes sil etila tseefe-osoiif o deel o yoeosp cdlssseefs r -f psefe o der ip oite oesileeor osoiifo sl f f - merouane , ahmed (sports creativity, 2025)
The class of physical and sports education crosses an important pedagogical component and complementary material in the educational system in Algeria, which is an integral part of general education, as it works to develop and nurture pupils "physically, psychologically and mentally", and form their personalities to contribute to building and building the country, and to achieve these major goals must be provided The necessary capabilities of playgrounds and educational aids, the preparation of qualified professors and the preparation of modern pedagogical curricula, and these professors must acquire sufficient knowledge information that makes them familiar with the pedagogical content masters of the knowledge that integrates within the newly approved curricula are able to translate them into teaching behavior during the course of physical and sports education